Impact of Climate Change on Crops Productivity Using MODIS-NDVI Time Series - Zainab K. Jabal; Thair S. Khayyun; Imzahim A. Alwan (Civil Engineering Journal, 2022)
Climate change is the single biggest threat facing the global food system. Irrefutable impacts of climate change on the food systems are recently acknowledged. Therefore, extensive scientific efforts around the globe are dedicated to investigating and evaluating the short and long-term effects of climate change on the development of global food systems. In this study, an integrated approach of two methodologies, including Moderate Resolution Imaging Spectroradiometer (MODIS) Data and Normalized Difference Vegetation Index (NDVI), was employed to extrapolate the long-term changes in agronomic areas from 2000 to 2020 in the Dukan Dam Watershed (DDW), Northern Iraq. The link between agricultural areas and the primary production of essential crops (Wheat, Barley, Rice, Maize, and Sunflower) is proposed to be altered due to the impact of climate change. According to the Intergovernmental Panel on Climate Change (IPCC) report, Iraq is one of the semi-arid regions in the world that has recently been characterized by water scarcity and limited agronomic areas. Three independent variables (rainfall, temperature, and agriculture area) were used in the multiple regression analysis to understand the impact of the main drivers affecting the production of crops in DDW. Obtained results showed an increasing trend in crop production as a result of the frequent use of groundwater and surface water sources along with the implementation of greenhouse cultivation. Correlation analysis shows that the crop production was significantly related to the annual precipitation with a 59–63% in winter crops like wheat and barley, but was less sensitive to the temperature with a 20–40% in summer crops like rice, maize, and sunflower. Doi: 10.28991/CEJ-2022-08-06-04 Full Text: PDF